Prevalence of hearing impairement in the district of Lucknow, India - Anupam Mishra; Veerendra Verma; Girish Kumar Shukla; Subhash Chandra Mishra; Raghav Dwivedi (Wolters Kluwer Medknow Publications, 2011)
A multi-cluster study (survey) was carried out by department of ENT KG Medical University, Lucknow from July 2003 to August 2004 in rural and urban population of Lucknow district to estimate prevalence and causes of hearing impairment in the community. Data included audiological profile and basic ear examination that was analysed through EARFORM software program of WHO. Overall hearing impairment was seen in 15.14% of rural as opposed to 5.9% of urban population. A higher prevalence of disabling hearing impairment (DHI) in elderly and deafness in 0-10 years age group was seen. The prevalence of sensorineural deafness necessitating hearing aids was 20% in rural and 50% in urban areas respectively. The presence of DHI was seen in 1/2 urban subjects and 1/3rd of rural counterparts. The incidence of cerumen / debris was very common in both types of population and the need of surgery was much more amongst rural subjects indicating more advanced / dangerous ear disease.